CHARACTER BUILDING DALAM KONSEP PENDIDIKAN IMAM ZARKASYI DITINJAU DARI FILSAFAT MORAL IBNU MISKAWAIH - Mu'minah, Najwa (Jurnal Filsafat "WISDOM", 2015)
Degradation of moral consciousness, especially in the politic and Indonesian government bureaucracy, in recent times that was pictured by various anomalies and immorality, such as a corruption, has become a negative â€œcultural normâ€, which seem very difficult to be controlled. The condition of national spirit and morality suggested the need of redevelopment of model of character education (character building) as a national healing. Imam Zarkasyi implemented several principles of character building in the Pesantren of Darussalam Gontor. He taught his pupils on the basis of the virtues of the excellences with refer to the Panca Jiwa and the Four Mottos of Modernity of the Pesantren as their living values. His reformative efforts in the context of contemporary Islamic education are actually intended to the development of character, in other words, â€œcharacter buildingâ€, by implementing the principle of the Golden Mean of Ibn Miskawaih. Some aspects of Zarkasyi's principles of education that might be supportive for developing the national character education program, and still relevant for today are: firstly, moral education should have the leadership insights; secondly, moral education should have the objective moral values as the teleological purposes; thirdly, moral education should be built through the best environment, in order to be optimized and efficient; and fourthly, moral education curriculum should be integrated and comprehensive. So, the Zarkasyi's concept of character building, and the education movement became the concept of character education that quite mature and should be extracted by our nation.